2020
DOI: 10.1111/jfpp.15148
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory quality of gluten‐free cakes supplemented with grape seed, pomegranate seed, poppy seed, flaxseed, and turmeric

Abstract: In this study, gluten‐free flour mixture (75% rice flour + 15% chickpea flour + 10% carrot flour) was replaced separately with 5% of grape seed, pomegranate seed, flaxseed, poppy seed, and turmeric to improve the nutritional composition of gluten‐free cakes. Incorporation of flaxseed and turmeric caused a decrease in the volume index compared to the gluten‐free control sample. The protein and fat content of the cake samples prepared with flaxseed and poppy seed were found to be higher than the gluten‐free cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The lowest inhibition value was 19.2, and it was observed in the case of 1.75% BG, 8.83% PG, and 38.78% WT samples, which proves that it was water that created conditions for the development of features influencing radical scavenging capacity. DPPH radical scavenging capacity values proving the antioxidant capacity resulted mainly from the addition of pomegranate and β-glucan because rice flour has a trace ability to inhibit DPPH radical scavenging capacityabout 8% [1]. The DPPH radical scavenging capacity test measures the ability of an extract to give hydrogen to the DPPH radical scavenging capacity, which causes the color of the DPPH radical scavenging capacity solution to fade.…”
Section: Effect Of Pomegranate and β-Glucan On Chemical Properties Of Muffinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest inhibition value was 19.2, and it was observed in the case of 1.75% BG, 8.83% PG, and 38.78% WT samples, which proves that it was water that created conditions for the development of features influencing radical scavenging capacity. DPPH radical scavenging capacity values proving the antioxidant capacity resulted mainly from the addition of pomegranate and β-glucan because rice flour has a trace ability to inhibit DPPH radical scavenging capacityabout 8% [1]. The DPPH radical scavenging capacity test measures the ability of an extract to give hydrogen to the DPPH radical scavenging capacity, which causes the color of the DPPH radical scavenging capacity solution to fade.…”
Section: Effect Of Pomegranate and β-Glucan On Chemical Properties Of Muffinsmentioning
confidence: 99%
“…The only known method of fighting celiac disease is to avoid products that may contain gluten. A gluten-free diet is often recommended for people who do not have celiac disease but suffer from other diseases like dermatitis herpetiformis, gluten ataxia, and wheat allergy [1][2][3][4]. For this reason, the gluten-free market is growing more dynamically.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, poppy cultivation for the food industry has a long tradition, especially in Central Europe (Fejer 2007).Poppy seeds contain almost no opium alkaloids. Contamination of the final product with opium alkaloids may occur as a result of inappropriate harvesting practices or the use of poppy seed that is a by-product of the cultivation of technical poppy cultivars intended for the pharmaceutical industry (López et al 2018).Poppy seeds are a source of valuable omega-6 fatty acids, contain a lot of minerals (Na, K, Mg, Ca), and the amount of protein exceeds 20% (Levent et al 2020, Senila et al 2020. The poppy seed oil also contains significant amounts of β-sitosterol (663.9-3 244.4 ppm), α-tocopherol (22.0-45.8 ppm), γ-tocopherol (195.4-280.9 ppm) (Erinç et al 2009), and β-tocopherol (309.5-567.3 ppm) (Özcan and Atalay 2006).The oil content of poppy seeds ranges from 28-52% depending on cultivar, seed colour, growing technology and environmental conditions (…”
mentioning
confidence: 99%
“…Poppy seeds are a source of valuable omega-6 fatty acids, contain a lot of minerals (Na, K, Mg, Ca), and the amount of protein exceeds 20% (Levent et al 2020, Senila et al 2020. The poppy seed oil also contains significant amounts of β-sitosterol (663.9-3 244.4 ppm), α-tocopherol (22.0-45.8 ppm), γ-tocopherol (195.4-280.9 ppm) (Erinç et al 2009), and β-tocopherol (309.5-567.3 ppm) (Özcan and Atalay 2006).…”
mentioning
confidence: 99%
“…This concentration did not fundamentally affect the sensory properties of the product [ 20 ]. The study conducted by Levent et al [ 22 ] found that the grape seeds had higher antioxidant properties compared to rice flour, chickpea flour, carrot flour, flaxseeds, pomegranate seeds and poppy seeds. Nakov et al [ 23 ] found that the addition of 4%, 6%, 8% and 10% of grape pomace powder statistically ( p < 0.05) increased the antioxidant activity of cakes.…”
Section: Resultsmentioning
confidence: 99%